(3GdNHQI GdbVGFjI aj GdbVGjG GdMbhbjI (B/s - (3Mja, eYJUe NGdO eMehOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2014)
(3jJfGhd cJGH (B((3GdNHQI GdbVGFjI aj GdbVGjG GdMbhbjI(B) (3hGdPj bGe HJCdjag (B((3eYJUe NGdO eMehO Mja(B) (3aj MhGdj (B(232) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdSdWI GdbVGFjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI(B: (3GdaUd GdChd (B: (3Gdeaghe GdbGfhfj ddNHQI GdbVGFjI, GdaUd GdKGfj (B: (3GdELQGAGJ GdbGfhfjI ddNHQI GdbVGFjI, GdaUd GdKGdK (B: (3eOi MLjI JbQjQ GdNHQI GdbVGFjI aj GdEKHGJ, GdedGMb, GdeQGLY(B.s
(3CUd GdcJGH QSGdI eGLSJjQ (B/ (3ETQGa GdCSJGP GdOcJhQ aGFb eMehO GdTeGY, LGeYI GdjQehc(B.s
(3HHdjhLQGajI (B: (3UaMI (B223-232.s
Keywords: (3GdSdWI GdbVGFjIs -- (3bhGfjf hJTQjYGJs; (3GdbVGAs -- (3bhGfjf hJTQjYGJs; (3GdNHQIs -- (3bhGfjf hJTQjYGJs